Analysis Of Job Satisfaction on Performance with Job Loyalty as An Intervening Variable (Case Study at BPJS Ketenagakerjaan All Medan Raya) - Dwi Qurbani, Sabda; Isa Indrawan, Muhammad (Lafadz Jaya Publisher, 2023)
This study aims to see whether Job Satisfaction affects performance and loyalty as a supporting variable positively or negatively and has no effect at all using a saturated sample technique. The total population of 118 will be used entirely as research samples using associative quantitative methods and collecting data using a questionnaire. and surveys, as well as using the Smart PLS 3.3 research tool. as a calculation medium and this research model uses Path analysis. The results of this study are Job Satisfaction has a negative effect on performance. It can be proven by this study with the results of Job Satisfaction having a negative and significant effect on performance as evidenced by the original sample value of -0.185 and p values of 0.002 <0.05. Job Satisfaction has a negative effect on Job Loyalty, which can be proven by this study. Job Loyalty has a positive and significant effect on performance. It can be proven by this research. Job Loyalty can be an intervening variable on Job Satisfaction and Performance negatively and significantly Job loyalty can be an intervening variable but negatively with the original sample results of -0.350 and p values of 0.000.